The Effects of Melatonin on the Descending Pain Inhibitory System and Neural Plasticity Markers in Breast Cancer Patients Receiving Chemotherapy: Randomized, Double-Blinded, Placebo-Controlled Trial - Palmer, Ana Claudia Souza; Souza, Andressa; dos Santos, Vinicius Souza; Cavalheiro, José Antônio Crespo; Schuh, Fernando; Zucatto, Angela Erguy; Biazus, Jorge Villanova; Torres, Iraci Lucena Da S.; Fregni, Felipe; Caumo, Wolnei (Frontiers in Pharmacology, 2019)
Background: Adjuvant chemotherapy for breast cancer (ACBC) has been associated with fatigue, pain, depressive symptoms, and disturbed sleep. And, previous studies in non-cancer patients showed that melatonin could improve the descending pain modulatory system (DPMS). We tested the hypothesis that melatonin use before and during the first cycle of ACBC is better than placebo at improving the DPMS function assessed by changes in the 0–10 Numerical Pain Scale (NPS) during the conditioned pain modulating task (CPM-task) (primary outcome). The effects of melatonin were evaluated in the following secondary endpoints: heat pain threshold (HPT), heat pain tolerance (HPTo), and neuroplasticity state assessed by serum brain-derived neurotrophic factor (BDNF), tropomyosin kinase receptor B, and S100B-protein and whether melatonin’s effects on pain and neuroplasticity state are due more so to its impact on sleep quality. Methods: Thirty-six women, ages 18 to 75 years old, scheduled for their first cycle of ACBC were randomized to receive 20mg of oral melatonin (n = 18) or placebo (n = 18). The effect of treatment on the outcomes was analyzed by delta (Δ)-values (from pre to treatment end). Results: Multivariate analyses of covariance revealed that melatonin improved the function of the DPMS. The Δ-mean (SD) on the NPS (0–10) during the CPM-task in the placebo group was −1.91 [−1.81 (1.67) vs. −0.1 (1.61)], and in the melatonin group was −3.5 [−0.94 (1.61) vs. −2.29 (1.61)], and the mean difference (md) between treatment groups was 1.59 [(95% CI, 0.50 to 2.68). Melatonin’s effect increased the HPTo and HPT while reducing the (Δ)-means of the serum neuroplasticity marker in placebo vs. melatonin. The Δ-BDNF is 1.87 (7.17) vs. −20.44 (17.17), respectively, and the md = 22.31 [(95% CI = 13.40 to 31.22)]; TrKB md = 0.61 [0.46 (0.17) vs. −0.15 (0.18); 95% CI = 0.49 to 0.73)] and S00B-protein md = −8.27[(2.89 (11.18) vs. −11.16 (9.75); 95% CI = −15.38 to −1.16)]. However, melatonin’s effect on pain and the neuroplastic state are not due to its effect on sleep quality. Conclusions: These results suggest that oral melatonin, together with the first ACBC counteracts the dysfunction in the inhibitory DPMS and improves pain perception measures. Also, it shows that changes in the neuroplasticity state mediate the impact of melatonin on pain. Clinical Trial Registration:www.ClinicalTrials.gov, identifier NCT03205033.